Testimonies of Noble Culture and Literature in 19th Century Letters - Bankauskaite, Gabija (Respectus Philologicus, 2025)
Židonis, Giedrius, Niewulis-Grablunas, Jowita, 2024. Nikodemas Erazmas Iwanowskis = Nikodem Erazm Iwanowski: Eliza Orzeszkowa, Maria Konopnicka: korespondencija ir prisiminimai: [Paragiai (Žemaitija) – Varšuva – Gardinas]. Kaunas: LSMU Kalbų ir edukacijos katedra, 327 p.This monograph is of significant interest and value within the contemporary cultural field, offering a comprehensive exploration of the subject matter and providing a foundation for further research. The decision to ​​present the text of the book in two languages ​​– Lithuanian and Polish – is highly commendable as it expands the circle of potential readers. The significance of intertwining languages ​​and cultures in Lithuania during that period is shown. The opportunity is provided to consider the phenomenon of noble culture, its diversity and change in the second half of the 19th century and the beginning of the 20th century. In the context of the panorama of Samogitia and Poland's social life, the correspondence between the Lithuanian artist Nikodem Erazm Iwanowski and the Polish writers Eliza Orzeszkowa and Maria Konopnicka is presented.
Keywords: 19th century; Nikodem Erazm Iwanowski; letters; Eliza Orzeszkowa; Maria Konopnicka; noble culture